Management of Acute Encephalitis - Nichols, Emma Hitt (MD Conference Express, 2014)
Multiple causes of encephalitis exist, including infectious and autoimmune agents. This article discusses the pathophysiology of acute encephalitis related to several more common forms of the disease.